Núcleo, centro de governo, centro presidencial, alto governo: Várias nomenclaturas e uma quest\~ao principal - Pedro Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– A subject that has gained prominence in the fields of political science and public administration is the Core of Government (CoG), that is, units and/or individuals responsible for the alignment and coordination of the main objectives of the president or first-minister. Although the topic has several names, a question still deserves to be better addressed: how do the planning, coordination and management of the Executive branch's priorities operate? However, the literature of CoG is still in early stage, especially in Brazil. In order to contribute to this debate, this paper develops a broad literature review with three primary goals: to present the concepts and findings of the international literature of core of government; to map the advances of the field of study of the Executive branch in Brazil and to indicate the future research agenda in the country. As a conclusion, the diversity of analytical strategies must be seen as constructive to the extent which there is a consensus that the frameworks' variations of the core of government are the rule, not the exception. In addition, the Brazilian case constitutes an excellent research laboratory on the Executive dynamics, due to its political-institutional particularities. Therefore, this research agenda tends to contribute to the description and explanation of how the political system operates and, above all, its effects on the decision-making processes and their outputs and outcomes in terms of public policies.
Keywords: H83; 330; core of government; coordination; Executive branch; Brazil